Towards Accessible Remote Work: Understanding Work-from-Home Practices of Neurodivergent Professionals - Das, Maitraye; Tang, John; Ringland, Kathryn E.; Piper, Anne Marie (CSCW 2021, 2021)
Working from home has become a mainstream work practice in many organizations during the COVID-19 pandemic. While remote work has received much scholarly and public attention over the years, we still know little about how people with disabilities engage in remote work from their homes and what access means in this context. To understand and rethink accessibility in remote work, the present paper studies work-from-home practices of neurodivergent professionals who have Autism Spectrum Disorder, Attention Defcit Hyperactivity Disorder, learning disabilities (e.g., dyslexia) and psychosocial disabilities (e.g., anxiety, depression). We report on interviews with 36 US-based neurodivergent professionals who have been working from home during the pandemic. Our fndings reveal that while working from home, neurodivergent professionals create accessible physical and digital workspaces, negotiate accessible communication practices, and reconcile tensions between productivity and wellbeing. Our analysis reconsiders what access means in remote work for neurodivergent professionals and ofers practical insights for inclusive work practices and accessibility improvements in remote collaboration tools.